2016
DOI: 10.1002/2016jc011723
|View full text |Cite
|
Sign up to set email alerts
|

Teleconnection between the North Indian Ocean high swell events and meteorological conditions over the Southern Indian Ocean

Abstract: The link between North Indian Ocean (NIO) high swell events and the meteorological conditions over the Southern Indian Ocean (SIO) is explored in this article, using a combination of in situ measurements and model simulations for the year 2005. High waves, without any sign in the local winds, sometimes cause severe flooding events along the south‐west coast of India, locally known as the Kallakkadal events and cause major societal problems along the coasts. In situ observations report 10 high swell events in N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 36 publications
5
24
0
Order By: Relevance
“…Nayak et al () found that the low‐frequency swells from the Southern Ocean reach the southern tip of Indian mainland in about 4 days without much energy dissipation. Our results agreed well with those of Remya et al (). In addition, the propagation speed of swells in the Indian Ocean was fastest (required the shortest time) in May and August, followed by November.…”
Section: Resultssupporting
confidence: 94%
See 4 more Smart Citations
“…Nayak et al () found that the low‐frequency swells from the Southern Ocean reach the southern tip of Indian mainland in about 4 days without much energy dissipation. Our results agreed well with those of Remya et al (). In addition, the propagation speed of swells in the Indian Ocean was fastest (required the shortest time) in May and August, followed by November.…”
Section: Resultssupporting
confidence: 94%
“…Furthermore, these swells cause high wave activity and sometimes Kallakkadal events along the NIO coastal regions. The overall propagation characteristic of SIOW‐related swells in this study is agreed with Remya et al ().…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations